Gospodarczo-militarne problemy i dylematy Związku Radzieckiego w latach 30. XX wieku: The economic and military problems and dilemmas of the Soviet Union in the 1930s - Klimiuk, Zbigniew (Przegląd Wschodnioeuropejski, 2019)
In December of 1927, the 15th Congress of the Communist Party of the Soviet Unionapproved the guidelines for the elaboration of a five-year plan of the economic development of the country. According to J. Stalin, “the basic task of the five-year plan was to set […] a technologically backward country – on the tracks of a new modern technology”. The idea entailed make the Soviet Union an industrial state, strong one as well as completely self-sufficient and independent of the capitalist world. At the same time, the task of transforming the country into an industrial state was combined with a different objective, namely to completely rid the economy of capitalist elements, which in turn was to lead directly to the creation of a socialist society. At the same time the creation of a modern industry was to serve as a basis for the retooling and reorganization of not only the industrial sector, but also of transport and agriculture in accordance with the precepts of socialism. In the case of the agricultural sector, the objective was defined as the transformation of agricultural holdings into large collective farms, which was supposed to lead to the creation of a socialist economic base in the countryside (with peasants being perceived as an obstacle for this effort), with the ultimate objective of preventing the restoration of capitalism in the Soviet Union. The five-year plan was also aimed at creating necessary economic and technical foundations which would allow to overtake the leading capitalist economies (United States, Great Britain, Germany, France, Japan) in the perspective of a few years (5–6 years). This objective was to be energetically pursued in order to be achieved at the turn of the first and second five year plan. However, the economic reality turned out to be more complicated and the strategy of “catching up and overtaking” was systematically delayed, which – unavoidably – stirred up irritation and rage in the circles of Joseph Stalin. The leap from the “kingdom of coercion” to the “kingdom of freedom” turned out to be a spectacular flop. Purges and terror (addressed also at the party-state apparatus, army and security organs) in the 1930s, which caused millions of victims, did not bring the expected economic effects. The engulfing atmosphere of threat and fear led to paralysis, which in turn resulted in declining PRZEGLĄD WSCHODNIOEUROPEJSKI X/1 2019: 163–186 164 Zbigniew Klimiuk economic efficiency. At that time, a distinctive barrier to economic growth surfaced in the Soviet economy, namely the impossibility of achieving an increase in production on the basis of existing assets, which was due to the quality of management and the inefficiency of the economic system. Economic growth was thus possible only through new investments – the phenomenon (known as the so-called investment pressure) which was besetting the socialist economies until their very end. The existence of such a barrier was also confirmed by the course of the implementation of the third (unfinished) five-year plan (for the period 1938–1942).